Uganda - Legal and Judicial Sector Study Report - World Bank (World Bank, 2012)
This study examines and evaluates developments in the Justice Law and Order Sector (JLOS) institutions, noting both the achievements and continuing challenges of reform under first phase Sector Investment Plan (SIP I) and SIP II. It pays particular attention to the SIP guidelines and objectives and to the outstanding challenges described in various reviews of the JLOS institutions, more specifically: (a) the commercial court; (b) the impact of the establishment of the centre for arbitration and dispute resolution on case backlogs; (c) the adequacy of legal education to meet the needs of the sector in view of recent reforms, and (d) the provision of legal aid services to the poor to increase their access to justice. The study also touches on the challenges identified by the JLOS Medium Term Evaluation (MTE), which warranted detailed study and which informed the development of SIP II. They include law reform, legal education, and access to justice for the poor and particularly in the conflicted areas of Uganda.